Gamification of Iqra’ to Strengthen Religious Literacy of Migrant Children - Muhammad Saifuddin Azzudy; Syamsul Arifin; Nurhafid Ishari (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education for Indonesian migrant children abroad often faces limitations in access, resources, and teacher availability, which weakens their religious literacy. Specific Background: At the Indonesian Education Center (PPWNI) Klang, Malaysia, the ability of children to read hijaiyah letters is hindered by monotonous methods and low motivation. Knowledge Gap: Previous studies have shown the effectiveness of gamification in general and formal education, but little research has examined its integration with the Iqra’ method in non-formal migrant contexts. Aims: This study investigates how gamification can be applied in Iqra’ learning for migrant children and evaluates its impact on motivation, discipline, participation, and literacy skills. Results: Using a qualitative case study with 30 students and one teacher, the findings reveal that gamification elements—such as points, scoreboards, challenges, and star rewards—improved attendance (from 70% to 90%), raised average scores (from 58 to 82), and enhanced confidence in reading aloud. Novelty: This research uniquely integrates gamification with the Iqra’ method in a non-formal migrant setting with limited resources, demonstrating effectiveness without relying on digital technology. Implications: The study contributes theoretically by offering a community-based gamification model and practically by providing an enjoyable and replicable solution for strengthening religious literacy among migrant children. Highlights: Gamification effectively boosts motivation, discipline, and literacy skills. Integrating Iqra’ with gamification in migrant settings is novel. Simple, low-tech strategies can improve learning outcomes significantly. Keywords: Gamification, Iqra’ Method, Religious Literacy, Migrant Children, Non-Formal Education